ANALYSIS OF SOCIAL PARTICIPATION, ELDER ABUSE, AND CORRESPONDING BEHAVIOR OF THE ELDERLY IN CHINA. (20th December 2022) - Feng, Guanggang; Jiang, Shumin
Abstract: Introduction: Ancient Chinese wisdom under the Confucian culture show that "Parents raise children who in turn support them in old age" and "Don't wash one's dirty linen in public". The elderly in China brings up children with the aim to guard against troubles in their late years, but many older people with sons also suffer from various forms of elder abuse, and often choose to submit to humiliation when facing abuse from family members. Data: The Survey on the living conditions of the elderly in urban and rural China（SSAPUR）, four waves: 2015, 2016, 2017 and 2018 followed samples(N=224360) Methods: The hierarchical Logit model was used to analyze the influence of social participation on elder abuse in China, and the risk of the elderly's choice to submit to humiliation. Results and conclusion: The results showed that the annual incidence of elderly abuse (include physical abuse, emotional abuse, financial abuse, and neglect of care) among the elderly in China was 5.36%, and 35.77% of them chose to submit to humiliation. The more the elder participate in society involvement outside the home, the less likely they are to be abused from family members, the less likely they submit to humiliation. The more sons, the higher the risk of elder abuse. Therefore，the relevant government and the grass-roots social organizations should strengthen the construction of social organizations for the elderly.